Program evaluation : alternative approaches and practical guidelines - Fitzpatrick, Jody L.; Sanders, James R; Worthen, Blaine R. (Boston : Allyn and Bacon, 2004)
This text helps both students and professionals who are new to evaluation to understand how the field has evolved, what different approaches an evaluator can take in conducting evaluations, and how to plan and conduct an evaluation. The text makes extensive use of checklists, examples, and a comprehensive case study. Finally, throughout the book, students are introduced to current trends and controversial issues in evaluation and ways to conduct evaluations in an ethical and professional manner.--BOOK JACKET
Includes bibliographical references and indexes
Keywords: Educational evaluation; Evaluation; Evaluation research (Social action programs)